An Analysis of E-Business Research Topics - Turan, Semen Son (INT Organization Center ACAD Research, 2015)
Due to its interdisciplinary nature and its pace in penetrating into various facets of everyday activities, ebusiness has become an increasingly popular topic over the last two decades. While early 1990s e-business research grounded in ICT (information communication technology) theories covered topics such as, internal systems capabilities, adoption, and technology investments' impact on success, the new millennium with the dot. com crash, witnessed a flux of interest in performance management, value creation and strategy formulation. Related intellectual capital literature grew, accompanied by technology mergers and acquisitions underscoring the need for valuing. digital capital.. This entire technological craze in adopting to change is necessitating the adoption of a futuristic vision on part of professionals and academicians. This paper attempts to offer a roadmap for interdisciplinary scholars by providing insight of what has been studied so far in e-business research, what topics face extinction due to technological advancement and what the future beholds for us in this realm. Its distinctiveness lies in its use of an integrated methodology combining broad literature review (spanning through the almost two decade-long lifetime of e-business literature between the years 1995-2013) and content analysis of 41 global e-business events organized by prominent academic and professional institutions in 2013. The trilingual (Turkish, English and German) keyword search process used in reaching current event information and the translation of such into English, may spearhead future studies of this kind. To the best of the knowledge at hand, this study is the first to provide a comprehensive literature review of past e-business research from a generalist perspective and utilize practitioners' event as a tool for forecasting future research topics.
Semen Son Turan (MEF Author)
##nofulltext##
Keywords: E-commerce; E-business research topics; E-business; Emerging topics in e-business